Mechanism controlling groundwater chemistry in the hyper-arid basin with intermittent river flow: insights from long-term observations (2001–2023) in the lower Heihe River, Northwest China - Zhang, Jialing; Wang, Ping; Liu, Shiqi; Yu, Jingjie (Frontiers in Environmental Science, 2024)
The geochemical processes of groundwater in arid regions are generally influenced by both natural hydrological processes and human activities. However, impacts of water-rock interactions on groundwater recharge via hydrological processes, controlled by both intermittent river water flow and groundwater withdrawals, is still poorly understood. In this study, 327 groundwater chemistry datasets collected from the upper, middle (including Gobi and riparian zones), and lower regions of the Ejina Delta in Northwest China from 2001 to 2023 were analyzed. Our results revealed that the total dissolved solids (TDS) concentration of groundwater in Ejina Delta ranged from approximately 881.5 ± 331.6 mg/L in the upper regions to 1953.6 ± 1208.5 mg/L in the lower regions, with an increasing trend observed. Ecological water conveyance (EWC), recharging aquifer through intermittent river water flow, resulted in a decrease in TDS concentrations from 2001 to 2023 mainly in the upper region. While irrigation notably affected groundwater chemistry in the lower region, resulting in a substantial increase in groundwater salinity. Groundwater chemistry in the Middle Gobi region remained relatively stable over the study period. Generally, the hydrochemical composition shifted from the Na-Mg-SO4-HCO3 and Na-Mg-Ca-SO4-HCO3 types in the upper region to Na-Mg-SO4-HCO3 and Na-Mg-SO4-Cl types in the lower region, with Na-SO4-Cl predominant in the Middle Gobi. These shifts were likely be attributed to the interplay of water-rock interactions, coupled with evaporation-crystallization processes. Inverse modeling using PHREEQC revealed that in the upper-middle region, primary water-rock interactions involved calcite dissolution and the precipitation of dolomite, gypsum, halite, and sylvite salts, as well as cation exchange reactions (2NaX+Ca2+→CaX2+2Na+). In contrast, the hydrogeological system in the middle-lower region exhibited an opposite pattern of water-rock interactions. Overall, ecological water conveyance partially facilitated water-rock interactions during lateral groundwater flow, while irrigation disrupted the natural hydrogeochemical equilibrium, involving halite dissolution and opposite cation exchange reactions compared to other regions.